2020
DOI: 10.3389/fimmu.2020.00169
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis Reveals Antiviral and Anti-inflammatory Effects of Puerarin in Piglets Infected With Porcine Epidemic Diarrhea Virus

Abstract: Collectively, these results indicate that PR could exert antiviral and anti-inflammatory effects in piglets infected with PEDV and have the potential to be an effective antiviral feed additive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 60 publications
7
29
1
Order By: Relevance
“…One study has shown the upregulation of genes for IL-1β, IL-6, IL-8, and TNF-α in IPEC-J2 cells infected with PEDV 29 . Consistently, we previously reported that the mRNA levels of related inflammatory factors in Vero cells and the levels of inflammatory factors in the ileal tissue are elevated in PEDV-challenged piglets 8 . However, blood circulation is vital in the development of systemic inflammation.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…One study has shown the upregulation of genes for IL-1β, IL-6, IL-8, and TNF-α in IPEC-J2 cells infected with PEDV 29 . Consistently, we previously reported that the mRNA levels of related inflammatory factors in Vero cells and the levels of inflammatory factors in the ileal tissue are elevated in PEDV-challenged piglets 8 . However, blood circulation is vital in the development of systemic inflammation.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, I-FABP could be used as a tissue-specific injury marker 43 , 44 . In our previous study, histologic lesions were present in the jejunum and ileum of PEDV-infected piglets, including severe villous atrophy 8 . In the present study, PEDV decreased plasma D-xylose and I-FABP concentrations, while increasing DAO activity in the plasma, indicating that PEDV induced intestinal dysfunction.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Diarrhea is the main cause of death of newborn and suckling piglets, which brings enormous economic loss to the pig industry [1]. The occurrence of piglet diarrhea is related to genetic and improper management, especially the infection of pathogenic microorganisms, such as Escherichia coli [2], Salmonella [3], Clostridium perfringens [4][5][6], porcine epidemic diarrhea virus [7], etc. Therefore, it is necessary to search for molecular markers of diarrhea resistance and carry out porcine disease-resistant breeding.…”
Section: Introductionmentioning
confidence: 99%